Is There a Nonlinear Relationship between Serum Uric Acid and Lipids in a Hypertensive Population with eGFR ≥30 ml/min/1.73 m2? Findings from the China Hypertension Registry Study. (18th September 2020) - Yu, Yu; Huang, Xiao; Li, Minghui; Ding, Congcong; Hu, Lihua; Zhong, Xiao; Zhou, Wei; Wang, Tao; Zhu, Lingjuan; Bao, Huihui; Cheng, Xiaoshu
Abstract : Background . Evidence regarding the nonlinear relationship between serum uric acid (SUA) and blood lipids in Chinese population with hypertension is limited. Therefore, the present study aimed to investigate whether there is a nonlinear association between SUA and lipids in Chinese hypertensive population with an estimated glomerular filtration rate (eGFR) ≥30 ml/min/1.73 m 2 . Methods . A total of 13, 355 hypertensive participants with eGFR ≥30 ml/min/1.73 m 2 were selected from the Chinese Hypertension Registry Study. Multivariate linear regression was used to examine the linear relationship between SUA and lipids. Smooth curve fitting (penalized spline method) and threshold saturation effects were used to analyze the nonlinear association between SUA and lipids. Results . In the fully adjusted model, the results showed a positive correlation between SUA and TG ( β  = 0.15; 95% CI: 0.14, 0.16) and LDL-C ( β  = 0.06; 95% CI: 0.05, 0.07), respectively. However, the relationship between SUA and HDL-C was nonlinear. The inflection point of SUA was 7.24 mg/dL. On the left side of the inflection point (<7.24 mg/dL), SUA was negatively associated with HDL-C ( β  = −0.02; 95% CI −0.02, −0.01). On the right side of the inflection point (≥7.24 mg/dL), SUA was not related to HDL-C ( β  = 0.01; 95% CI −0.01, 0.02). Conclusion . After adjusting for all covariates, SUA was positively associated with TG and LDL-C. The relationship between SUA and HDL-C was nonlinear. The negative correlation between SUA and HDL-C only existed when the SUA was less than 7.24 mg/dL in a hypertensive population with eGFR ≥30 ml/min/1.73 m 2 .